2000
DOI: 10.1111/j.1435-5597.2000.tb00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of new firm success

Abstract: Abstract. The differences between new firms, even the differences present right at the start, may affect their life course and success over time. This article addresses the determinants of success of Dutch start‐ups from a longitudinal perspective. After an overview of the literature on both the definition of success and the success factors of new firms we test how new firm characteristics relate to firm growth in number of employees using a panel of nearly 2,000 firms. In addition to a large firm size right f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 19 publications
1
35
0
5
Order By: Relevance
“…Les cinq variables les plus discriminantes, tant dans la littérature théorique que dans les études empiriques, sont les suivantes : le capital humain général (Brüderl, Preisendörfer et Ziegler, 1992 ;Cooper, Gimeno-Gascon et Woo, 1994 ;Marvel, 2007 ;Thompson, 2007 ;Wiklund et Shepherd, 2001 ;Wright et al, 2007), l'expérience de l'entrepreneur (Agarwal et al, 2004 ;Filion, 1997 ;Schutjens et Wever, 2000), les activités préparatrices à la création (Brüderl, Preisendörfer et Ziegler, 1992 ;Castrogiovanni, 1996 ;Hansen, 1995 ;Lussier et Pfeifer, 2000), la motivation de l'entrepreneur (Laufer, 1975 ;Lumpkin et Dess, 1996 ;Miles et al, 1978 ;Miner, 1990 ;Sternberg, 2004 ;Wicklund, 1999) et son implantation géographique (Lasch, Le Roy et Yami, 2005a ;Kangasharju, 2000 ;Marchesnay, 1998 ;Tödtling et Wanzenböck, 2003). Nous avons donc décidé d'utiliser ces cinq variables pour tenter de construire une typologie des entrepreneurs dans les TIC.…”
Section: Les Variables Discriminantes Des Typologiesunclassified
See 1 more Smart Citation
“…Les cinq variables les plus discriminantes, tant dans la littérature théorique que dans les études empiriques, sont les suivantes : le capital humain général (Brüderl, Preisendörfer et Ziegler, 1992 ;Cooper, Gimeno-Gascon et Woo, 1994 ;Marvel, 2007 ;Thompson, 2007 ;Wiklund et Shepherd, 2001 ;Wright et al, 2007), l'expérience de l'entrepreneur (Agarwal et al, 2004 ;Filion, 1997 ;Schutjens et Wever, 2000), les activités préparatrices à la création (Brüderl, Preisendörfer et Ziegler, 1992 ;Castrogiovanni, 1996 ;Hansen, 1995 ;Lussier et Pfeifer, 2000), la motivation de l'entrepreneur (Laufer, 1975 ;Lumpkin et Dess, 1996 ;Miles et al, 1978 ;Miner, 1990 ;Sternberg, 2004 ;Wicklund, 1999) et son implantation géographique (Lasch, Le Roy et Yami, 2005a ;Kangasharju, 2000 ;Marchesnay, 1998 ;Tödtling et Wanzenböck, 2003). Nous avons donc décidé d'utiliser ces cinq variables pour tenter de construire une typologie des entrepreneurs dans les TIC.…”
Section: Les Variables Discriminantes Des Typologiesunclassified
“…L'expérience de l'entrepreneur est également une variable très fré-quemment retenue (Agarwal et al, 2004 ;Filion, 1997 ;Schutjens et Wever, 2000). Elle regroupe la qualification de l'entrepreneur (Cooper, GimenoGascon et Woo, 1994), ses expériences professionnelles antérieures (Brüderl, Preisendörfer et Ziegler, 1992), son expérience dans la branche d'activité au sein de laquelle il crée (Praag, 2003) et son passé entrepreneurial (Cooper, Gimeno-Gascon et Woo, 1994).…”
Section: Les Variables Discriminantes Des Typologiesunclassified
“…Most studies on success determinants distinguish between firm-internal and external factors (Storey, 1994;Schutjens and Wever, 2000;Davidsson et al, 2010;Risselada and Schutjens, 2017). Numerous academic studies have shown that it is the characteristics of firms and entrepreneurs that are the primary 'firminternal' drivers of firm success and firm growth, either as direct influences through entrepreneurial competences (Tamásy, 2006), management or strategic experience, or financial capital (Santarelli and Vivarelli, 2007), or indirect via personality factors that lead to ambitions for firm growth, which in turn is a prerequisite for firm success (Davidsson, 1991;De Tienne et al, 2008; for recent overviews, see Gilbert et al, 2006;Davidsson et al, 2010;Blackburn et al, 2013;Van Witteloostuijn et al, 2015).…”
Section: Literature Overview and Hypothesesmentioning
confidence: 99%
“…Drawing from the observed general trend of firms and industrial activity to be spatially concentrated in certain locations (Gordon and McCann 2000), and the unanimous understanding of entrepreneurship as a complex notion with multiple empirical manifestations, entrepreneurship dynamics have been studied in various disciplines, ranging from economics and economic geography to sociology and psychology (Schutjens and Wever 2000;Audretsch et al 2002;Gordon and McCann 2000). The dynamics of co-location or else, agglomeration economies, have been studied in economic theory, following the seminal works of Weber (1909Weber ( /1929 and Marshall (1925), in economic geography with a special focus on cost reduction (Krugman 1991;Venables 1996) and in the sociological strand of literature largely evolving around Granovetter's (1985;1992) work on the relationship between social networks of communication and information exchange that might transcend firm and industry boundaries, thus affecting their operation and performance.…”
Section: Entrepreneurship and The Region: Some Theoretical Consideratmentioning
confidence: 99%